Theoretical perspectives in operations management: an analysis of the literature. Issue 8 (3rd August 2015) - Walker, Helen; Chicksand, Daniel; Radnor, Zoe; Watson, Glyn
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – It is important to advance operations management (OM) knowledge while being mindful of the theoretical developments of the discipline. The purpose of this paper is to explore which theoretical perspectives have dominated the OM field. This analysis allows the authors to identify theory trends and gaps in the literature and to identify fruitful areas for future research. A reflection on theory is also practical, given that it guides research toward important questions and enlightens OM practitioners. Design/methodology/approach – The authors provide an analysis of OM theory developments in the last 30 years. The study encompasses three decades of OM publications across three OM journals and contains an analysis of over 3, 000 articles so as to identify which theories, over time, have been adopted by authors in order to understand OM topics. Findings – The authors find that the majority of studies are atheoretical, empirical, and focussed upon theory testing rather than on theory development. Some theories, such as the resource-based view and contingency theory, have an enduring relevance within OM. The authors also identify theories from psychology, economics, sociology, and organizational behavior that may, in the future, have salience to explain burgeoning OM research areas such as servitization and sustainability. Research limitations/implications – The study makes a novel contribution by exploring which main theories have been adopted or developed in OM, doing so by systematically analyzing articles from the three main journals in the field (the Journal of Operations Management, Production and Operations Management, and the International Journal of Operations and Production Management), which encompass three decades of OM publications. In order to focus the study, the authors may have missed important OM articles in other journals. Practical implications – A reflection on theories is important because theories inform how a researcher or practicing manager interprets and solves OM problems. This study allows the authors to reflect on the collective OM journey to date, to spot trends and gaps in the literature, and to identify fruitful areas for future research. Originality/value – As far as the authors are aware, there has not been an assessment of the main theoretical perspectives in OM. The research also identifies which topics are published in OM journals, and which theories are adopted to investigate them. The authors also reflect on whether the most cited papers and those winning best paper awards are theoretical. This gives the authors a richer understanding of the current state of OM research.